Tautomer Structures in Ketose–Aldose Transformation of 1,3-Dihydroxyacetone Studied by Infrared Electroabsorption Spectroscopy - Chen, Szu-Hua; Hiramatsu, Hirotsugu (The journal of physical chemistry. B, 2019)
The acyclic form of monosaccharides exists in a structural equilibrium, with aldose having the aldehyde group and ketose the ketone group (ketose–aldose equilibrium). A basic catalyst facilitates their transformation, which affects the chemical properties of the monosaccharide. In this study, we investigated the ketose–aldose transformation of 1,3-dihydroxyacetone (1,3-DHA), one of the simplest systems of the ketose–aldose equilibrium. We examined the effects of piperidine as the basic catalyst and used IR electroabsorption spectroscopy to study the responses to an external electric field. We analyzed the changes in IR absorption by considering the changes in the molecular orientation and number of molecules in response to the external electric field. The results of the analysis revealed the permanent dipole moment μP, an angle η between μP and μT (the transition moment of the molecular vibration), and the equilibrium constants. The ketose–aldose transformation of 1,3-DHA can be explained in terms of the equilibrium of three states. In the presence of piperidine, a five-state equilibrium was concluded. On the basis of the experimental data, we propose plausible models of dihydroxyacetone, E-enediols, Z-enediol, or glyceraldehyde for each state. The results of our structural analysis of these tautomers provide a detailed understanding of the ketose–aldose transformation of acyclic saccharides and the effects of the basic catalyst.